Biomass-Derived Carbonaceous Materials to Achieve High-Energy-Density Supercapacitors - Karamanova, Boryana; Shipochka, Maria; Georgiev, Martin; Stankulov, Toma; Stoyanova, Antonia; Stoyanova, Radostina (Frontiers in Materials, 2021)
Biomass-derived carbonaceous materials are considered as one of most perspective electrodes for symmetric supercapacitors working with alkaline-basic electrolytes. However, they still exhibit lower energy density. Herein, we demonstrate the capacitance performance of the commercial carbon product (YP-50F, “Kuraray Europe” GmbH), obtained from coconuts, in symmetric supercapacitors by using lithium and sodium organic electrolytes. It is found that YP-50F delivers higher energy density when lithium electrolyte containing LiBF4 salt is employed. Sodium electrolyte with NaPF6 salt is less aggressive towards YP-50F than that of LiPF6 salt, as a result of which a good capacitance performance is observed in sodium electrolyte. The contributions of surface functionality groups of YP-50F, as well as its compatibility with non-aqueous lithium and sodium electrolyte, are discussed on the basis of post-mortem SEM/EDS and X-ray photoelectron spectroscopy (XPS) data analyses. The obtained correlations could be of significance in order to design sustainable supercapacitors with high-energy density.